p38MAPK/MK2 signaling stimulates host cells autophagy pathways to restrict Salmonella infection - Suwandi, Abdulhadi; Menon, Manoj B.; Kotlyarov, Alexey; Grassl, Guntram A.; Gaestel, Matthias (Frontiers in Immunology, 2023)
Autophagy plays an important role in recognizing and protecting cells from invading intracellular pathogens such as Salmonella. In this work, we investigated the role of p38MAPK/MK2 in modulating the host cell susceptibility to Salmonella infection. Inhibition of p38MAPK or MK2 led to a significant increase of bacterial counts in Salmonella infected mouse embryonic fibroblasts (MEFs), as well as in MK2-deficient (Mk2-/-) cells. Furthermore, western blot analysis showed that Mk2-/- cells have lower level of LC3 lipidation, which is the indicator of general autophagy compared to Mk2-rescued cells. In Mk2-/- cells, we also observed lower activated TANK-binding kinase-1 phosphorylation on Ser172 and p62/SQTM1-Ser403 phosphorylation, which are important to promote the translocation of p62 to ubiquitinated microbes and required for efficient autophagy of bacteria. Furthermore, immunofluorescence analysis revealed reduced colocalization of Salmonella with LC3 and p62 in MEFs. Inhibition of autophagy with bafilomycin A1 showed increased bacterial counts in treated cells compared to control cell. Overall, these results indicate that p38MAPK/MK2-mediated protein phosphorylation modulates the host cell susceptibility to Salmonella infection by affecting the autophagy pathways.